Analysis Of The Implementation Of Goverment Expenditure, Cost Benefit And Political Economy On the Indoneisa’s Peacekeeping - Mastina Nopela; Hikmat Zakky Almubaroq; Ari Pitoyo Sumarno (CV. AFDIFAL MAJU BERKAH, 2024)
Peacekeeping missions are integral to global stability, with Indonesia actively participating in these endeavors. As a nation dedicated to promoting international harmony, Indonesia acknowledges the need for meticulous planning and analysis in utilizing government funds for peacekeeping, recognizing the complexity of this process (Sanchez, 2018). The article's primary purpose is to provide a comprehensive analysis of the implementation of government expenditure, cost-benefit considerations, and the influence of political economy factors on Indonesia's peacekeeping missions. Three key objectives guide this exploration: first, to scrutinize the intricate details of government expenditure implementation, evaluating transparency, accountability, and efficiency. Second, to assess the pivotal role of cost-benefit analysis in decision-making processes, quantifying both financial and non-financial aspects to guide optimal resource allocation. Lastly, to delve into the multifaceted political economy factors influencing peacekeeping outcomes, considering domestic elements like public opinion, political dynamics, and economic considerations. The scope is tailored to Indonesia's peacekeeping context, analyzing how government funds are allocated, examining the impact of cost-benefit analysis on decision-making, and understanding the political and economic factors that shape peacekeeping outcomes. The structured order of discussion ensures a logical progression from an overview to a detailed analysis of affecting factors, challenges, findings, and recommendations. By fulfilling these objectives, the article aims to contribute valuable insights that can enhance the effectiveness of Indonesia's peacekeeping missions and the efficient utilization of government funds in this crucial global endeavor.